Getting Lost Behavior in Patients with Mild Alzheimer’s Disease: A Cognitive and Anatomical Model - Yatawara, Chathuri; Lee, Daryl Renick; Lim, Levinia; Zhou, Juan; Kandiah, Nagaendran (Frontiers in Medicine, 2017)
Background: Getting lost behavior (GLB) in the elderly is believed to involve poor top-down modulation of visuospatial processing, by impaired executive functions. However, since healthy elderly and elderly with Alzheimer’s disease experience a different pattern of cognitive decline, it remains unclear whether this hypothesis can explain GLB in dementia. Objective: We sought to identify whether poor executive functions and working memory modulate the relationship between visuospatial processing and prevalence of GLB in healthy elderly and patients with Alzheimer’s disease. Complementary to this, we explored whether brain regions critical for executive functions modulate the relationship between GLB and brain regions critical for visuospatial processing. Method: 92 participants with mild Alzheimer’s disease and 46 healthy age-matched controls underwent neuropsychological assessment and a structural MRI. GLB was assessed using a semi-structured clinical interview. Path analysis was used to explore interactions between visuospatial deficits, executive dysfunction/working memory and prevalence of GLB, in Alzheimer’s disease and controls independently. Results: For both healthy controls and patients with mild Alzheimer’s disease, visuospatial processing deficits were associated with GLB only in the presence of poor working memory. Anatomically, GLB was associated with medial temporal atrophy in patients with mild Alzheimer’s disease, which was not strengthened by low frontal grey matter volume as predicted. Instead, medial temporal atrophy was more strongly related to GLB in patients with high frontal grey matter volumes. For controls, GLB was not associated with occipital, parietal, medial temporal or frontal grey matter volume loss. Conclusion: Cognitively, a top-down modulation deficit may drive GLB in both healthy elderly and patients with mild Alzheimer’s disease. This modulation effect may be localized in the medial temporal lobe for patients with mild Alzheimer’s disease. Thus, anatomical substrates of GLB in mild Alzheimer’s disease may not follow the typical top-down modulation mechanisms often reported in the healthy aging population. Implications advance therapeutic practices by highlighting the need to target both working memory and visuospatial deficits simultaneously, and that anatomical substrates of GLB may be disease-specific.